AN ANALYSIS OF STUDENTS’ ANXIETY AND SELF-EFFICACY IN WRITING AT ENGLISH DEPARTMENT OF HALU OLEO UNIVERSITY - Lena, Nur; Jaya, Amir; Mursalim, Mursalim (Universitas Halu Oleo, 2019)
Anxiety is one of students' problems in writing. Students with high anxiety have enormous impact on their writing outcomes. The purpose of this study was to find out the students anxiety in writing and their self-efficacy categories. This study employed survey design. The sample of this study was the students of the fourth semester in writing III course which consisted of 33 students. The data were collected by using close-ended questionnaire and interview guide. The close-ended questionnaire was analyzed by using SPSS 16 version while interview was analyzed descriptively. The result showed that cognitive anxiety was dominant category of writing anxiety and unity was dominant category of writing self-efficacy experienced by the students.Keywords: Students Anxiety, Students Self-Efficacy, Writing Performance.